AUTOCAD CIVIL 3D UNTUK PENGOLAHAN DATA XYZ DAN EKSPORT DXF DALAM MENGHITUNG VOLUME BATUAN - Jarwanto; Yefriansyah Salim; Ahmad Zaki Zakaria (Nusantara Hasana Journal, 2024)
Awangbangkal District, Karangintan District, Banjar District, South Kalimantan Province in 2000 was different from 2023. Old coordinate data that is still in manual shape and only x, y and z data, can be merged with new data. Both data can be combined to identify developments or changes in the area due to prolonged material harvesting activities. Autocad Civil 3D as the software used can change the manual data of x, y and z to digital data by entering data into Microsoft Excel continued with Notepad as a data bridge so that it can be read by AutoCad Civile 3D with pre-made PENZD format. The coordinate points x, Y and z already entered in AutoCAD Civil 3 D can be made contours and cross-cutting. Ten cross-sectional overlays made between the old data and the new data, resulting in differences between them. The divide resulted in a total of 456,000 cubic meters of material that had been taken between 2000 and 2023. Data formatted by autocad with extension dwg can be transferred to extension dxf to be read by other software from Minescape, Terramodel, 12D, Surpac.